Infection-Induced Kidney Diseases - Narayan Prasad; Manas Ranjan Patel (Frontiers in Medicine, 2018)
Infection induced kidney diseases are of concern for clinicians because timely detection and treatment of infections may cure or limit the extent of injury inflicted by microorganisms causing the infections. Infections can cause kidney injury by either direct invasion, or indirectly by immune mediated mechanisms, which manifest as post-infectious glomerulonephritis, or infection-related glomerulonephritis. Clinical manifestations may be acute or chronic depending on the microorganisms, endemic/epidemic nature and source of infection. All microbials virus, bacteria, mycobacteria, fungus, and protozoa have been implicated in kidney diseases either causing direct kidney injuries or immune-mediated injuries. Infection control practices in large parts of world is limited by poverty, social behavior, high population density, deforestation, inadequate access to safe drinking water, and poor health care facilities. Although, antimicrobials and vaccinations have successfully eradicated and cured many infectious diseases; however injudicious antimicrobial use and emergence of resistant organisms complicated the disease severity like secondary renal amyloidosis with chronic persistent infection. Re-emergence of various infections has been a recent pattern in developed world leading to uncertain diagnostic challenges, and association with kidney diseases.